(untitled) (Bangladesh Journal of Medical Biochemistry, 2017)
In addition to its well known role on mineral homeostasis, vitamin-D has many diverse actions including anti-inflammatory, relaxation of vascular smooth muscle cells and downregulation of renal renin production. Deficiency of Vitamin-D is a treatable condition that has been found to be associated with coronary artery disease. This study was carried out to assess the vitamin-D status in acute myocardial infarction (AMI) patients. Active form of vitamin-D (1, 25-OH D3, calcitriol) does not reflect vitamin-D status due to its short plasma half life. 25-OH D3 or calcidiol is considered as circulating reservoir and is used to assess vitamin-D status due to its long plasma half life. In this study 25-hydroxycholecalciferol [25 (OH)D3] was assessed in 40 acute myocardial infarction patients and 40 age- and sexmatched healthy subjects. Serum 25-hydroxycholecalciferol and Lipid profile parameters were estimated. Data were analyzed with the help of SPSS version 20.0. Vitamin-D was found to be significantly reduced in AMI patients when compared with that of Controls which were 28.50±16.68 ng/l in cases and 38.32±16.47 ng/l in Controls, p=0.011. Blood pressure, total Cholesterol and LDL-Cholesterol were found significantly higher in AMI compared to those among healthy controls. Among all study subjects, statistically significant positive correlation of 25(OH)D3 was found with HDL-C (p=0.014). Significant negative correlation was found with serum TC (p=0.001) and LDL-C (p <0.001). Serum TG was found negatively correlated with 25-hydroxycholecalciferol but it was not statitiscaly significant (p=0.068). In our study Vitamin-D deficiency was found to be significantly associated with myocardial infarction, dyslipidemia and hypertension. Bangladesh J Med Biochem 2015; 8(2): 55-59